(untitled) (Journal of the College of Basic Education, 2023)
The student of the history of Islamic jurisprudence in general and the jurisprudence of the Twelver Shiites in particular must take a pause for contemplation in front of the news from the Twelver Shiites. Fundamentalists put it to derive the legal ruling such as unanimity, reason and analogy.